HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DENGAN PERILAKU SADARI SEBAGAI UPAYA DETEKSI DINI KANKER PAYUDARA - Nurrohmah, Ianatus Shofya; Yati, Dwi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
The incidence of breast cancer in Indonesia has increased from year to year as many as 12,014 cases (28.7%). If this cannot be controlled, it is estimated that by 2030 there will be 26 million people suffering from breast cancer and 17 million people who will die. The number of breast cancer case that is still quite high is caused by the low awareness of women to do examination immediately if there is something different in their breasts. One of the early detection efforts is by doing Breast Self- Examination (BSE). This research was aimed at finding out the relationship between the level of knowledge of Breast Self- Examination (BSE) and BSE behavior as breast cancer early detection effort of Nursing undergraduate students of Health Faculty of Universitas Jenderal Achmad Yani Yogyakarta. The research was quantitative in nature with descriptive correlation design and cross sectional approach. The sample taken used purposive sampling with 68 respondents. The instrument of the research used questionnaire about BSE knowledge and BSE behavior and the result would be analyzed with Pearson statistical test. The results showed that the majority age of respondents 20.78 years old, obtained information facilities from other people and mass media, had knowledge average of 16.95 and the behavior average of 24.56.The research result showed that there was significant relationship between BSE knowledge and BSE behavior proven by the p value of 0.028 (p < 0.05). The Pearson correlation value was 0.266 showing positive correlation with weak correlation. There was a relationship between BSE knowledge and BSE behavior. The higher the level of knowledge of BSE, the better BSE behavior. The nurses could increase the attention to the health education to increase the BSE behavior.   Keywords: Knowledge, Behaviour, Breasts Cancer, Breast Self- Examination (BSE)